2017
DOI: 10.1002/ejlt.201600410
|View full text |Cite
|
Sign up to set email alerts
|

Algerian Moringa oleifera whole seeds and kernels oils: Characterization, oxidative stability, and antioxidant capacity

Abstract: The rising of global per capita food consumption has driven scientists and manufacturers into a search for new or renewed edible oil sources, while also improving their production towards maximum yield, quality, and economic feasibility. Hence, a new origin (Algerian) of Moringa oleifera seed oil was characterized in the present study in terms of its physical and chemical features on two consecutive crops. Moreover, aiming to ascertain if the industrial solvent extraction could be enhanced, extracted oils from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…Sánchez-Machado et al (2006) found α-tocopherol as the main isomer in M. oleifera leaves (744.5 µg/g) from Sonora, Mexico. The Algerian M. oleifera oil sample from kernels showed a significant higher value of total tocopherol (287-327 mg/kg), as well as the individual amounts of α-tocopherol (195.8-263.2 mg/kg), β-tocopherol (4.7-10.5 mg/kg), γ-tocopherol (51.2-77.8 mg/kg), and δtocopherol (6.1-8.6 mg/kg) (Boukandoul et al, 2017). This higher content could be due to the fact that the previous authors use different plant parts, which certainly contain a higher content of this lipophilic vitamin.…”
Section: Chemical Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Sánchez-Machado et al (2006) found α-tocopherol as the main isomer in M. oleifera leaves (744.5 µg/g) from Sonora, Mexico. The Algerian M. oleifera oil sample from kernels showed a significant higher value of total tocopherol (287-327 mg/kg), as well as the individual amounts of α-tocopherol (195.8-263.2 mg/kg), β-tocopherol (4.7-10.5 mg/kg), γ-tocopherol (51.2-77.8 mg/kg), and δtocopherol (6.1-8.6 mg/kg) (Boukandoul et al, 2017). This higher content could be due to the fact that the previous authors use different plant parts, which certainly contain a higher content of this lipophilic vitamin.…”
Section: Chemical Characterizationmentioning
confidence: 97%
“…Recently, it has attracted a lot of attention due to its nutritional value, as also health benefits (David et al, 2017) such as, inflammation treatments, diabetes, gastro-intestinal and infectious diseases along with cardiovascular, hematological, and hepatorenal disorders (David et al, 2017;Gopalakrishnan, Doriya, & Santhosh, 2016). The reason why it has been introduced in many parts of the world, including Algeria, where it is cultivated in some Saharan areas (Bachar and tamanrasset), is mainly due to its food security and nutritional proposes (Boukandoul, Casal, Cruz, Pinho, & Zaidi, 2017). Edible leaves and seeds of M. oleifera (eaten fresh, powdered or cooked) contain a varied profile of many nutrients, such as essential sulfur amino acids, protein and minerals (Maryann, Lord, Uchechukwu, & Chibuike, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Table 5. Seed oil main components of the most known Moringa species [11,18,36,38,48,[60][61][62][63]67,70,76,[80][81][82][83]. From a health point of view, the oil is also rich is phytosterols, consistently between 0.2 and 0.6 g/100 g oil, being rich in β-sitosterol, stigmasterol, campesterol and ∆5-avenalsterol [71].…”
Section: Seed Oil Content and Compositionmentioning
confidence: 99%
“…Table 1. Moringa species origin, distribution, preservation status and major uses [1,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, industrial oil extraction procedures include a shelling step, producing two residues: The shells and fat exhausted kernel. We have previously compared the quality of M. oleifera oil obtained directly from unshelled seeds flour (Boukandoul, Casal, Cruz, Pinho, & Zaidi, 2017), in opposition to its extraction from shelled seed, with very attractive outcomes. In line with this, a study comparing the chemical composition of both defatted M. oleifera flours obtained after oil extraction from whole seeds and kernels would be of great interest and complementary to the previous study.…”
Section: Introductionmentioning
confidence: 99%